The Effect of Body-Weight Support Treadmill Training on Muscle Morphology and Glucose Tolerance in Individuals with a Spinal Cord Injury - Stewart, Brian (My University, 2002)
Skeletal muscle is the primary site of glucose disposal in the body, and consequently plays a predominant role in the regulation of blood glucose levels after the ingestion of a meal. Following spinal cord injury (SCI), skeletal muscles below the level of an upper motor neuron lesion undergo marked changes in muscular properties that affect glucose tolerance. Recent studies on individuals with a SCI have reported improved glucose tolerance following periods of electrically-stimulated training. This appears to result from improved muscle morphology and post-exercise insulin sensitivity, and increased GLUT 4 content, enzyme activity, and muscle fiber capillary number. It might be expected that the weight-bearing and greater muscular involvement associated with body-weight support treadmill training (BWSTT) would have an even more profound effect on previously observed responses. The purpose of this study was to investigate whether 6 months of BWSTT improved whole-body glucose tolerance and some of the muscular parameters that are expected to influence glucose metabolism, in a group of 9 individuals with an incomplete SCI. A leg biopsy and a resting, 3 hour oral glucose tolerance test (OGTT) were performed on each subject before and after 6 months of training. Analysis of the muscle biopsy revealed significant increases in post-training muscle fiber size for type I (P=0.01) and type IIa (P=0.05) fibers in comparison to pre-training values. A significant increase in type IIa fiber proportion (P=0.03) and a significant decrease in type IIx fiber proportion (P<0.01) were found following training. In addition, significant increases in post-training GLUT 4 protein content (P<0.01), citrate synthase protein content (P<0.01), and citrate synthase activity (P=0.01) were found in comparison with pre-training values. No change was found in the number of capillaries per fiber after training. Plasma insulin area under the time curve (AUC) during the post-training OGTT significantly decreased (P=0.04) in the subjects as a result of BWSTT. Despite the large decrease in plasma insulin concentration, blood glucose AUC also showed a significant decrease (P<0.01) during the post-training OGTT, indicating a training-induced increase in insulin sensitivity occurred in the subjects. According to the findings, we can speculate that the increase in insulin sensitivity was a result of the increase in muscle GLUT 4 content in the exercised muscles, possibly in combination with an increase in leg muscle mass, as indicated by an increased muscle fiber cross-sectional area. The results are the first in this field to provide evidence that BWSTT leads to beneficial morphological and metabolic changes in skeletal muscle fibers that improve glucose tolerance.
Keywords: weight; morphology; muscle; glucose; spinal cord; treadmill training